MARKETING APLICADO À FARMÁCIA - HEEMANN, A. C. W.; GARIPPE, G. M. (Visão Acadêmica, 2002)
O marketing deveria ser aplicado como instrumento de trabalho para auxiliar o farmacêutico na prestação da atenção farmacêutica e não apenas confundido com vendas e propagandas de medicamentos. MARKETING CONCERNING OF PHARMACY Abstract Marketing would be applied like a tool of work to help the pharmaceutical in the pharmaceutical attention and not only confused with sales and promotion of medicines.